Aspects of the labour market for new graduates in Ireland: 1982-1997 - Lydon, Reamonn (Economic & Social Studies, 1999)
Using a survey on the first destinations of award recipients in higher education from 1982 to 1997, the trend in first destinations and starting salaries for primary level graduates in Ireland is studied. The data show that despite large increases in supply throughout the 1980s, the average real wage received by recent graduates increased by 25 per cent over the decade. This phenomenon is explained by a combination of rising emigration and increasing demand during the period. With the onset of economic recession in 1990 and lower levels of emigration and demand, the real wage fell between 1990 and 1995. The paper finds that the increase in supply during this period was the main reason for the fall in real wages.
Keywords: Labour market; Graduate employment; Ireland